Aplikasi Teori Easterlin di Kabupaten Jember: The Application of the Easterlin Theory in Jember Regency - Mohammad Saleh (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2003)
In agrarian regions of developing countries, the assumed inverse relationship between rising income and declining fertility—central to Easterlin’s modernization theory—often remains unverified because traditional socioeconomic structures persist. This study challenges Easterlin’s (1983) framework by examining whether household income influences fertility directly or indirectly through family planning participation, using a sample of working wives in Jember Regency, Indonesia. Primary data were collected from 500 respondents selected via proportional cluster sampling across three economic zones (urban, suburban, peripheral). Path analysis was used to test two structural models: the effect of income on family planning use, and the combined effects of income and family planning use on fertility (number of living children). The findings show that household income has a significant positive direct effect on fertility. Family planning participation has a negative but non-significant effect, and the indirect pathway via family planning does not reverse the positive income-fertility relationship. These results contradict Easterlin’s prediction that higher income reduces fertility through a shift toward child quality. The study concludes that in lower-middle-income agrarian contexts, pronatalist norms—such as “many children bring fortune”—persist, overriding modernization effects. Recommendations include strengthening active family planning outreach, expanding non-formal education, and raising awareness of the impact of early marriage. Di daerah agraris negara berkembang, hubungan terbalik yang diasumsikan antara peningkatan pendapatan dan penurunan fertilitas—yang menjadi inti teori modernisasi Easterlin—sering kali tidak terbukti karena struktur sosial-ekonomi tradisional yang masih kuat. Penelitian ini menguji kerangka Easterlin (1983) dengan menganalisis apakah pendapatan keluarga mempengaruhi fertilitas secara langsung atau tidak langsung melalui partisipasi keluarga berencana (KB), menggunakan sampel istri yang bekerja di Kabupaten Jember, Indonesia. Data primer dikumpulkan dari 500 responden melalui cluster sampling proporsional dari tiga zona ekonomi (urban, suburban, pinggiran). Analisis jalur digunakan untuk menguji dua model: pengaruh pendapatan terhadap partisipasi KB, serta pengaruh pendapatan dan KB terhadap fertilitas (jumlah anak hidup). Hasilnya menunjukkan bahwa pendapatan keluarga berpengaruh positif signifikan secara langsung terhadap fertilitas, sementara partisipasi KB menunjukkan pengaruh negatif namun tidak signifikan. Temuan ini bertentangan dengan prediksi Easterlin bahwa pendapatan lebih tinggi mengurangi fertilitas melalui pergeseran ke kualitas anak. Penelitian ini menyimpulkan bahwa di wilayah agraris kelas menengah ke bawah, norma pro-natalis seperti “banyak anak banyak rejeki” masih dominan. Rekomendasinya adalah penguatan motivasi KB aktif, peningkatan pendidikan non-formal, dan penyuluhan usia kawin pertama.